Strategy for Making a Superior Quenchbody to Proteins: Effect of the Fluorophore Position - Jeong, Hee-Jin (MDPI, 2014)
Antibody-based sensors have made outstanding contributions to the fields of molecular biology and biotechnology. Our group recently developed a novel powerful fluorescent immunosensor strategy named Quenchbody (Q-body), which has been applied to the detection of a range of antigens in a rapid, simple, and sensitive manner. However, there were some Q-bodies whose fluorescence response was limited, especially for detecting protein antigens. With the aim of improving this issue, here we made twelve types of Q-bodies incorporated with different number and position of TAMRA fluorophore in the single chain Fv of HyHEL-10, an anti-hen egg lysozyme antibody, as a model. By measuring the fluorescence intensity and its antigen dependency, it was revealed that V(L)-V(H) type Q-bodies labeled at a non-CDR loop region of the V(L) shows the highest fluorescence response. This position locates close to the quenching Trp35 in V(L), while it is far from Trp residues in the bound antigen. This result clearly suggests the importance of dye position to maximize the fluorescence quenching and antigen-dependent de-quenching. The discovery may open a way to make many other Q-bodies with superior response.